Ultraviolet protection of weft-knitted fabrics. Issue 1 (2nd January 2016) - Wong, Wai-Yin; Lam, Jimmy Kwok-Cheong; Kan, Chi-Wai; Postle, Ronald
Abstract : Increased incidence of skin cancers worldwide has expedited the development and research of ultraviolet (UV)-protective clothing. Clothing acting as a 'second skin' for human beings provides a more durable protection against harmful UV radiation than sunscreen creams. The market value of UV-protective clothing is worth considering. This paper will provide important information to textile designers, manufacturers, and consumers about the production and selection of UV-protective knitwear. Although various factors that affect UV protection of fabrics have been studied by researchers, most of them focused on woven fabrics and chemical approaches for improving UV protection. Knitwear in the form of daily wear is an indispensable form of clothing in summer but there has been limited research concerning the UV-protective properties of weft-knitted fabrics to date, in particular the influence of fabric construction on UV protection factor (UPF) and fabric structural properties. This issue of Textile Progress reviews the major factors that affect UV protection by fabrics, including fibre types, yarn characteristics, fabric construction, colouration, chemical additives, wetness (rather than just the moisture absorbed into the fibres), the stretching that may occur in clothing, and the effects of laundering. Methods for evaluating the UV-protective ability of fabrics are also addressed. There is also an attempt to fill a research gap by investigating the influence of different knitted structures on a fabric's UPF, through incorporation of the three major stitch types in weft-knitted fabric constructions, namely the knit, tuck, and miss stitches.